Mystical Rationalism and Idealism - Wildan Setiawan (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
This article examines the relationship between rationalism, mysticism, and idealism within the philosophy of science as three epistemological approaches shaping human understanding of reality and knowledge. Rationalism emphasizes reason as the foundation of epistemic certainty through logical principles, while mysticism introduces a transrational dimension of knowledge obtained through intuition and spiritual experience. Idealism functions as a philosophical synthesis bridging reason and consciousness by positioning the subject as an active agent in the construction of knowledge. This study employs a qualitative library research method using philosophical and interpretative analysis of Western philosophical works and Islamic epistemological thought. The findings indicate that integrating rationality and spirituality produces an integrative scientific paradigm that transcends positivistic reductionism and fosters dialogue between science, philosophy, and religion. Consequently, mystical rationalism and idealism offer an alternative epistemological foundation for developing a more holistic and humanistic philosophy of science.